Skepticism in the Recognition of Traditional Knowledge for Public Policy Management Related to Climate Change - Gomel Apaza, Zenón Porfidio; Ishizawa Oba, Jorge; Granados Carbajal, Rafael Evelio; Gamwell, Adam (Revista Geográfica de América Central., 2024)
The investigation aimed to identify the contribution of traditional knowledge in the construction and management of public policies for biodiversity conservation and adaptation to climate change. It was based on two studies conducted between 2015 and 2017 in two indigenous rural communities situated above 3,910 meters above sea level in the northern Puno region of Peru. The results have been synthesized to generate a proposal for strategic guidelines for high mountain agriculture with a focus on adaptation to climate change. The identified categories of traditional knowledge encompass: a) soil, b) water, c) plant health, d) measures against hailstorms, e) measures against frost, f) organization and ritual, and g) varieties and mixtures tolerant to climatic extremes.A workspace is the community itself. In the absence of public policies that take into consideration the promotion of traditional knowledge, the community establishes guidelines and actions rooted on traditional knowledge of biodiversity conservation and adaptation to climate change in plans of life aligned with the local worldview, with the aim of escalating to the district level.  A workspace is the community itself, which in the absence of public policies that take into consideration the promotion of traditional knowledge, establish guidelines and actions based on traditional knowledge of biodiversity conservation and adaptation to climate change in plans of life based on the local worldview, with the aim of escalating to the district level.